ANALYSIS OF PROJECT-BASED LEARNING MODELS IN IMPROVING CRITICAL THINKING SKILLS OF ELEMENTARY SCHOOL STUDENTS - Resta Carlina; Eka Kartika; Eko Fajar Suryaningrat; Yeni Indriati Widyaningsih; Ejen Jenal Mutaqin (SOSIOEDUKASI, 2026)
This study aims to explore in depth the implementation of Project-Based Learning (PjBL) in improving elementary school students’ critical thinking skills. The research employed a qualitative approach with an intrinsic case study design conducted in a public elementary school in Indonesia. Participants consisted of one classroom teacher and ten fifth-grade students selected through purposive sampling. Data were collected through semi-structured interviews, participatory observation, and documentation, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, combined with thematic analysis procedures. The findings reveal four main themes: (1) construction of understanding through authentic problem exploration, (2) collaborative dynamics and reflective dialogue, (3) transformation of the teacher’s role as a cognitive facilitator, and (4) internalization of reflective attitudes in project completion. The study demonstrates that PjBL fosters analytical reasoning, evaluation of alternatives, inferential thinking, and metacognitive reflection through contextual and collaborative learning experiences. The results highlight that the effectiveness of PjBL is not solely reflected in measurable outcomes but also in the meaningful learning processes that shape students’ critical dispositions. This study contributes theoretically to strengthening the integration of social constructivist theory and critical thinking frameworks, and practically provides insights for teachers in designing reflective and dialogic learning environments at the elementary level.